Loss of the Perforin Cytotoxic Pathway Predisposes Mice to Experimental Cytomegalovirus Retinitis - Dix, Richard D. (American Society for Microbiology, 2003)
AIDS-related human cytomegalovirus (HCMV) retinitis continues to be a chronic ophthalmologic problem among human immunodeficiency virus type 1 (HIV-1)-infected patients who do not respond to highly active antiretroviral therapy. Although HCMV retinitis occurs during HIV-1-induced immunosuppression, the precise effector mechanism(s) that fails during the immunopathogenesis of AIDS to allow onset and progression of HCMV retinal disease remains unclear. We therefore performed a series of experiments to explore the relative roles of distinct pathways of lymphocyte-mediated cytotoxicity in either resistance or susceptibility to experimental murine cytomegalovirus (MCMV) retinitis in mice. Whereas mutant C57BL/6 mice deficient in the Fas/FasL cytotoxic pathway (gld mice) were identical to normal C57BL/6 mice and exhibited absolute resistance to retinal necrosis following subretinal MCMV inoculation, knockout C57BL/6 mice deficient in the perforin cytotoxic pathway (PKO mice) were susceptible to MCMV retinitis. Susceptibility of PKO mice to MCMV retinitis correlated with increased ocular MCMV titers when compared with ocular MCMV titers of gld and normal mice. Since mice with retrovirus-induced immunodeficiency syndrome (MAIDS) exhibited a frequency and severity of MCMV retinitis that were equivalent to those observed in PKO mice, we hypothesized that susceptibility to MCMV retinitis during MAIDS correlates with a decrease in the perforin cytotoxic pathway. To test this hypothesis, we developed a quantitative competitive reverse transcription-PCR assay to measure mouse perforin mRNA levels in the splenic T lymphocytes and MCMV-inoculated eyes of normal mice or mice with MAIDS. Perforin mRNA levels in splenic T lymphocytes were significantly decreased during MAIDS, by ∼100-fold, from perforin mRNA levels in normal mice. Moreover, MCMV-inoculated eyes destined to develop retinitis during MAIDS also showed a significant decrease in perforin mRNA levels from the perforin mRNA levels of MCMV-inoculated eyes of normal mice destined to be resistant to retinitis. As expected, perforin mRNA could not be detected in unmanipulated and uninfected eyes of normal mice. These results provide the first evidence that the perforin cytotoxic pathway is more important than the Fas/FasL cytotoxic pathway in providing resistance to experimental MCMV retinitis and that loss of the perforin cytotoxic pathway predisposes to MCMV retinitis.